PERANCANGAN ALAT BANTU SERVICE SEPEDA YANG ERGONOMIS DENGAN METODE REVERSE ENGINEERING (STUDI KASUS UMKM TERAS38IKE) - Fadhel Muhammad W; Sukania, I Wayan; Adianto (Universitas Tarumanagara, 2023)
Teras38ike is an MSME that operates in the bicycle maintenance sector. Ergonomics problems are one of the main factors faced. Bicycle maintenance activities at UMKM Teras38ike have caused many physical complaints while working and after work. Therefore, this situation must be corrected immediately. The focus of the research is to improve worker posture by designing ergonomic work aids. Workers' complaints are measured using 3 methods, namely Nordic Body Map, Quick Exposure Check and Rapid Entire Body Assessment. Based on the results of the analysis of physical complaints, the bicycle assembly aids were then redesigned based on ergonomic principles. The best designs are realized in prototype form. Based on the results of testing on the prototype, data showed that there was a decrease in the physical complaints of operators tasked with maintaining bicycles, namely by a decrease in the score on the Nordic Body Map, Quick Exposure Check and Rapid Entire Body Assessment.